Abstracts from the World Scientific Congress of Golf VII, Gold Coast, Queensland, Australia, September 5-7, 2014 (International Journal of Golf Science, 2015)
Keynote speakers at the 2014 WSCG: Professor Mark Broadie Carson Family Professor of Business and Vice Dean, Columbia Business School Dr. Debbie Crews Sport Psychology Consultant, Arizona State University Mr. David Darbyshire Physical Preparation Coach for Adam Scott, Movement Solutions International Pty Ltd Adjunct Professor Phillip Di Bella Business and Marketing; owner of Di Bella Coffee, author of Entrepreneurial Intelligence Professor Senshi Fukashiro Professor of Biomechanics, University of Tokyo, Japan Professor Sandy Gordon Professor of Sport and Exercise Psychology, The University of Western Australia Professor Mario LaFortune Head of Innovation at Nike, United States Associate Professor Shaun O`Leary Specialist Musculoskeletal Physiotherapist, Research Fellow, University of QLD Professor Eric Wallace Director of Sports and Exercise Sciences, University of Ulster, UK 70 podium presentations from some of the best golf researchers from around the world. Including the likes of Andrea Fradkin, John Hellstrom, David Lindsay, Sasho Mackenzie, Paul Grimshaw, Mark Cole, Pat Thomas, Martin Toms, Sean Horan .... 20 posters from emerging & innovative golf researchers & coaches.The WSCG also provides opportunity for emerging researchers & pilot data to be presented & discussed.